Formulation and Evaluation of Melphalan Nanosponges - Barish, Barish; Muthukumar, S.; Kavinkumar, V.; Rudrank, Shukla; Murthy, B. R. Srinivas; Santhanakumar, M.; Mumtaj Begum, S. M.; Indhumathi, M. L.; Abirami, A.; Kader Ashik, K. M. Abdul; et al. (Journal of Neonatal Surgery, 2025)
Nanosponges are a new type of nano structured materials which have been widely used for resolving many physical biological and chemical problems related with the treatment of disease. Melphalan is a drug which has been used for the formulation of novel drug delivery systems (NDDS) called nanosponges. The synthesized nanoparticles have been characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), and infrared spectrophotometer (IR) spectroscopy. The morphology of the nanostructures has been studied by using SEM, TEM, and IRspectrometry.Theresultsshowthattheobtainednanoscalestructuresare sub-micron in dimension and with a spherical shape. It is found that the drug is soluble in the alkaline solution and Ethanol and insoluble in Acetone and Water. The in-vitro release of the drug was found to be higher in the inclusion complex. The absorption values of Melphalan were 0.1686, 0.3624, 0.5357, 0.6963, 0.8770, 1.0693, 1.2700and1.4516respectively.In the calibration curve, linearity was obtained between5-40g/ml concentration of Melphalan and the regression value was R2 = 0.9996. The nano scale characterization technique should be used to a larger extent to identify the nano scales at disease sites in affected organs or tissues and to establish relevant interaction mechanisms.